Tes 1: (WACANA TAFSIR TEOLOGIS NEGARA ISLAM) - Ahmad Hafidh Alkaf (Sekolah Tinggi Agama Islam (STAI) Sadra, 2018)
This article aimed at the discourse of theological interpretation of the Islamic state. In the map of Islamic thought, the activity that accommodates Muslim intellectual stretches is interpretation. Tafsir al-Qur'an as an interpretation of the text has existed since the time Muhammad saw. lived until now. In its journey, the interpretation of the Qur'an experienced different developments and characteristics from time to time. The development of interpretation is generally divided into three periods: classical, middle, and modern (contemporary). And the discussion in this paper is on the contemporary position. In this phase, there is a tendentious interpretation. In other words, many of its interpreters interpret the Qur’an not to understand the Qur’an, but to defend the interests of its subjectivity. One of the types of interpretation as above is the interpretation of theological style.